BANK-SPECIFIC AND MACROECONOMIC DETERMINANTS OF NON-PERFORMING LOANS (NPLS) IN GHANA: THE CASE OF LISTED BANKS ON THE GHANA STOCK EXCHANGE - Daniel Amoah; Doris Boakye; Desmond Ofori; Adwoa Agyeiwaah Ampomah-Britwum (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study investigates the determinants of NPLs in Ghana's listed banks, addressing critical research gaps on credit risk analysis in emerging markets. Following Ghana's banking sector reforms and the lack of comprehensive frameworks, this study integrates bank-specific and macroeconomic factors to provide a complete understanding of NPL determinants within the banking sector. Using panel data from seven banks listed on the Ghana Stock Exchange (2010-2020), the study employs random effects regression validated through Hausman testing, integrating Financial Intermediation Theory and Moral Hazard Theory. The model demonstrates strong explanatory power (R-squared = 0.606), revealing significant negative relationships between NPLs and bank-specific variables: Capital Adequacy Ratio (-0.728), Loan-to-Deposit Ratio (-1.075), Return on Equity (-0.436), and Bank Size (-3.935). Bank Size emerges as the most influential determinant, confirming the presence of economies of scale in risk management. The counterintuitive LDR-NPL relationship suggests that aggressive lending is associated with more stringent credit screening procedures. Macroeconomic analysis confirms credit risk's countercyclical nature, with GDP (-1.773) and Money Supply (-1.821) significantly reducing NPLs. The Lending Rate and Inflation show positive but insignificant effects. Practical evidence from recent bank failures validates findings regarding capital adequacy. The study’s contributions include multi-framework integration, robust econometric analysis, and evidence-based recommendations for capital enhancement and risk-based pricing models. Findings highlight the integration of NPL management approaches to address institutional practices and macroeconomic conditions, with implications for banking supervision and monetary policy coordination in emerging economies.